THE OPTIMIZATION STRATEGY OF FISHERY WASTE IN SUMENEP REGENCY AS A VALUE-ADDED PRODUCT BASED ON THE CIRCULAR ECONOMY - Alvin Arifin; Moh. Sofwan Kastir Al Aziz; Liahmad Liahmad; Novi Wahyuningtias; Naila Tsawaba (LPPM STIE Muhammadiah Bandung, 2025)
The fisheries sector in Sumenep Regency plays a vital role in food security and the local economy, but generates substantial waste, including fish heads, bones, viscera, and skins. Most of these residues are discarded into the sea or landfills, creating environmental burdens and economic losses. This study aims to formulate a strategy for optimizing fishery waste based on circular economy principles using a sequential explanatory mixed-methods approach. The quantitative phase employed multiple linear regression to examine the effects of business duration, technology, and average catch on waste utilization. Results indicate that technology significantly influences utilization (p < 0.01), whereas business duration and catch volume are not significant. The qualitative phase, involving in-depth interviews and focus group discussions, reinforced these findings by revealing that limited access to simple processing technologies, weak market linkages, and inadequate regulations remain the main obstacles. Nevertheless, respondents recognized the potential of fish waste to be converted into organic fertilizer, animal feed, fish oil, and collagen. This study concludes that appropriate technology, market access, and regulatory as well as multi-stakeholder collaboration are crucial for implementing a circular economy model in Sumenep’s fisheries sector. The practical implication suggests strengthening community capacity and policy support to advance sustainable fishery waste valorization.